Bird Diversity of Poplar (Populus deltoides) based Agroforestry System in Ludhiana, Punjab - kumar, manoj (Indian Journal of Agroforestry, 2023)
Birds have a very close association with trees. Trees offer a platform to birds for nesting, roosting, foraging, breeding and feeding purposes. The introduction of agro-forestry system in Punjab as an alternative source of income to famers in addition to traditional farming income. Agro-forestry can effect or modify inherent species richness, communal alignment and species abundance, as well as species relationships and communal structure of particular areas. agro-forestry system have been found to influencing species diversity and as a common agent of evolutionary traps. The present paper discusses the avian community response in relation to agro-forestry plantation having Poplar Populus deltoids species plantation in Punjab. The study was conducted at two selected locations in district Ludhiana.Â A total of 43 bird species falling under 12Â orders and 24 families were recorded during the study. Passeriformes (30.23%) was the dominant order of bird species observed. Avian diversity at Location I and II were recorded to be 37 and 28 birds species respectively were observed. Out of 43 bird species 86.04% were resident, 11.62% were resident migrant and 2.32% was migrant in nature. Â Based upon their foraging behaviour, 18.6 % bird species were purely insectivorous and 13.95 % were granivores in nature. Further, it was recorded that 88.37% of the species observed were those who prefers agricultural landscape near human habitation. The presence of such diverse number of species in agro-forestry system signifies the importance of such system in sustaining the bird diversity in intensive agriculture practices being followed in Punjab. Thus we can say that agro-forestry system is playing role in sustenance of avian diversity, although it promotes species specific population abundance.